Escherichia coli phylogenetic and antimicrobial pattern as an indicator of anthropogenic impact on threatened freshwater mussels - Varandas, Simone (2023)
Freshwater bivalves are widely used as accumulation indicators and monitoring tools for assessing contaminant effects on different levels of biological integration. This pilot study aimed to explore the phylogenetic diversity of Escherichia coli isolated from freshwater mussels (Margaritifera margaritifera and Potomida littoralis) and characterize their phenotypes and antibiotic resistance profiles. Samples were collected in the Rabaçal and Tua Rivers, in the Douro basin, Portugal—two sites representing different levels of anthropogenic contamination. Antimicrobial susceptibility testing was performed via the disk diffusion method with 21 antibiotics. Results showed that 31% of isolates were multidrug-resistant (MDR). Thus, freshwater mussels provide an effective and time-integrated approach for identifying/quantifying fecal indicators, including MDR bacteria. PCR-based assays were designed for assessing phylogenetic E. coli groups. Among the E. coli isolates, the highest prevalence (44%) was observed in group D or E, followed by group E or Clade I (25%), group A (19%), and group B1 (13%). E. coli isolated from M. margaritifera predominantly exhibited a higher prevalence of phylogroups D or E, whereas E. coli from P. littoralis showed associations with phylogroups E or clade I, B1, A, and D or E. Our results provide new insights into the phylogenetic diversity of E. coli in freshwater bivalves. Additionally, the findings highlight the possible linkage of phylogroups with the host species, the geographical location in the water stream, and human activity. Using E. coli as a bioindicator isolated from freshwater mussels helps us grasp how human activities affect the environment. This study has important implications for those interested in safeguarding water resources, especially in tackling antibiotic resistance in aquatic ecosystems.